The extermination of prairie dogs in Kansas - Worswick, Jay G. (My University, 1905)
Introduction: For the past ten or fifteen years the prairie dog has been a torment to the farmer as well as the stock raiser of the Great Western Plains. In Kansas this pest has annoyed the farmers beyond endurance and many attempts toward its extermination have been made, but the majority of such undertakings have been to a great extent unsuccessful. Perhaps the most satisfactory among early experiments was the use of carbon bisulphid gas. The work was carried on something as follows: Carbon bisulphid is a very poisonous gas and when the liquid form is exposed to the air it soon passes into the gaseous state and fills all available space; experimenters found in this property an advantage and proceeded to make use of this simple fact. The work of destruction by this agent was done mostly by contractors who would go to the farmer and agree to kill all the dogs on his land for a certain sum of money; and the farmer seeing the advantage of being rid of the dogs, would usually accept the proposition. The contractor would then begin operations. He would appear in the field with a great quantity of cotton, flax straw etc., and a few bottles of carbon bisulphid; as he confined his work mostly to the larger towns it was not at all inconvenient for him to work from a wagon, driving a little distance when necessary in order to make his material available. A bunch of cotton about the size of a man’s fist would be saturated with the liquid and immediately thrust into the burrow; an end-gate rod would be used to force it down a distance of two or three feet, and as quickly as possible the opening of the burrow would be filled with the flax straw; this was the most essential part of the work, it being necessary to make the opening air tight so that when the gas escaped it would be forced back into the bottom of the burrow and the prairie dogs would soon be suffocated.
Citation: Worswick, Jay G. The extermination of prairie dogs in Kansas. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Prairie dogs; Extermination; Carbon Bisulphid gas; Kansas; Theses